Using scaffolding to support CLM students' critical multiple perspective-taking on history. (September 2021) - Hemmler, Vonna L.; Kibler, Amanda K.; van Hover, Stephanie; Carlock, Russell H.; Fitzpatrick, Colleen
Abstract: American classrooms are becoming increasingly diverse, yet curricula and pedagogies often do not meet diverse student needs. This is problematic for history education, long accused of presenting a historical perspective that excludes members of non-dominant groups. Using scaffolding and Critical Race Theory, we explore how two teachers addressed this issue by facilitating students' multiple, critical perspective-taking on American history through the use of scaffolding practices that exposed students to multiple perspectives and enriched their interactions with the content. We address why this approach is necessary for culturally and linguistically marginalized students before presenting implications and suggestions for further research. Highlights: Teachers utilized designed-in scaffolding to provide CLM students with multiple, critical perspectives on American history. Teachers engaged in contingent scaffolding to facilitate students' encounters with these perspectives on American history. This scaffolding supported students in bringing their marginalized identities into the classroom and curricular interactions.